Language-Based Caching of Dynamically Generated HTML - Brabrand, Claus; Møller, Anders; Olesen, Steffan; Schwartzbach, Michael I. (BRICS Report Series, 2001)
Increasingly, HTML documents are dynamically generated by interactive Web services. To ensure that the client is presented with the newest versions of such documents it is customary to disable client caching causing a seemingly inevitable performance penalty. In the <bigwig> system, dynamic HTML documents are composed of higher-order templates that are plugged together to construct complete documents. We show how to exploit this feature to provide an automatic fine-grained caching of document templates, based on the service source code. A <bigwig> service transmits not the full HTML document but instead a compact JavaScript recipe for a client-side construction of the document based on a static collection of fragments that can be cached by the browser in the usual manner. We compare our approach with related techniques and demonstrate on a number of realistic benchmarks that the size of the transmitted data and the latency may be reduced significantly.